Patient‐reported outcomes of implant placement performed concomitantly with transcrestal sinus floor elevation or entirely in native bone. Issue 2 (8th January 2016) - Franceschetti, Giovanni; Rizzi, Alessandro; Minenna, Luigi; Pramstraller, Mattia; Trombelli, Leonardo; Farina, Roberto
Abstract: Aim: Based on the hypothesis that maxillary sinus floor elevation with a transcrestal approach (tSFE) does not increase the morbidity of implant surgery, the study evaluated the patient‐reported outcomes as well as the type and incidence of complications when implants are placed either concomitantly with tSFE (performed according to Trombelli et al. 2008, 2010a, b) or entirely in native bone. Methods: Data from the record charts of patients undergone implant placement for single‐tooth rehabilitation in the posterior maxilla were retrospectively obtained from four clinical centers. Cases for tSFE group were included if they showed an extent of sinus lift ≥4 mm concomitantly to implant placement. Cases for N group were included when implant placement was performed entirely in native bone. Patient‐reported outcomes had been assessed using 100‐mm visual analog scales (postoperative pain, VASpain ) and visual rating scales (level of discomfort, VRSdiscomfort ; willingness to undergo the same surgery, VRSwillingness ). The dose of analgesics had been self‐recorded. Results: A convenience sample of 14 patients and 17 patients (contributing with one implant site each) treated with tSFE and N, respectively, was obtained for this study. Membrane perforation occurred in 1 tSFE case, without compromising the completion of the procedure. VASpain remained low (<12) in both groups. A tendency of VASpain to decrease with time was observed in both groups. The area under the curve for VASpain (AUCpain ), indicating the level of pain experience through the first week following surgery, was 18.0 (IR: 8.5–85.0) and 11.5 (IR: 4.5–18.5) in tSFE and N groups, respectively, with no significant inter‐group differences ( P = 0.084). The dose of analgesics was similarly low between groups. No significant inter‐group difference in VRSdiscomfort and VRSwillingness was observed. Conclusions: Implant placement performed either concomitantly with tSFE (according to Trombelli et al. 2008, 2010a, b) or entirely in native bone is associated with limited incidence of complications, low postoperative pain and medication and are both well tolerated.